Forecasting property price indices in Hong Kong based on grey models. Issue 3 (3rd July 2017) - Tan, Yongtao; Xu, Hui; Hui, Eddie C. M.
ABSTRACT: The real estate market in Hong Kong plays an important role in its economy. The property prices have been increasing a lot since 2009, which have become a major concern. However, few studies have been done to forecast the property price indices in Hong Kong. In this paper, two grey models, GM(1, 1) and GM(0, N), are introduced for the forecasting. The results show that GM(1, 1) has a better performance when forecasting with stable trend data, while GM(0, N) is more suitable for forecasting data in fluctuating trend. The sensitivity analysis for GM(0, N) shows that Population(POP) and Best Lending Rate(BLR) are significantly sensitive factors for data in stable trend. While for the fluctuating data, sensitivity of each factor presents uncertainties. This study also compares the forecasting performance of grey models with the ANN model and ARIMA model. The study demonstrates that grey models are more suitable for forecasting the Hong Kong property price indices than others.